2013
DOI: 10.1093/nar/gkt840
|View full text |Cite
|
Sign up to set email alerts
|

Human telomeres that carry an integrated copy of human herpesvirus 6 are often short and unstable, facilitating release of the viral genome from the chromosome

Abstract: Linear chromosomes are stabilized by telomeres, but the presence of short dysfunctional telomeres triggers cellular senescence in human somatic tissues, thus contributing to ageing. Approximately 1% of the population inherits a chromosomally integrated copy of human herpesvirus 6 (CI-HHV-6), but the consequences of integration for the virus and for the telomere with the insertion are unknown. Here we show that the telomere on the distal end of the integrated virus is frequently the shortest measured in somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
158
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(170 citation statements)
references
References 50 publications
12
158
0
Order By: Relevance
“…Even though the formal integration mechanism has yet to be demonstrated experimentally, sequencing of ciHHV-6A/B indicates that the TMR of the DR R of the genome is fused to the host chromosome telomeric repeats with loss of pac2 sequence from DR R . Such a structure is compatible with HR-mediated viral integration (5,30,31).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Even though the formal integration mechanism has yet to be demonstrated experimentally, sequencing of ciHHV-6A/B indicates that the TMR of the DR R of the genome is fused to the host chromosome telomeric repeats with loss of pac2 sequence from DR R . Such a structure is compatible with HR-mediated viral integration (5,30,31).…”
Section: Discussionmentioning
confidence: 97%
“…Analysis of the integrated virus genome revealed that the perfect TMR of the DR R region are fused to the host chromosome accompanied by a loss of the pac2 sequence, consistent with an integration mediated by HR between the viral TMR and the host telomere (5). At the other end of the viral genome, the pac1 region is also lost and additional telomeric repeats are added, suggesting that the TMR in DR L is a substrate for the generation of a new telomere (29)(30)(31).…”
mentioning
confidence: 78%
“…The mechanisms by which HHV-6A and HHV-6B integrate into the telomeric/subtelomeric junction of host chromosomes remain unclear. Analysis of the viral genome of iciHHV-6A ϩ /B ϩ individuals indicates that all HHV-6A/B open reading frames are largely intact, with no gross rearrangements (17). However, the pac1 sequence from DR L and the pac2 sequence from DR R are lost during the integration process (17).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the viral genome of iciHHV-6A ϩ /B ϩ individuals indicates that all HHV-6A/B open reading frames are largely intact, with no gross rearrangements (17). However, the pac1 sequence from DR L and the pac2 sequence from DR R are lost during the integration process (17). This is unlikely to have major impacts on the ability of HHV-6A/B to generate infectious virions, considering that invasion of the telomeric 3= overhang into the internal HHV-6A/B DR R -T1 could facilitate the release of a complete viral genome from the chromosome with a single reconstituted DR (17).…”
Section: Discussionmentioning
confidence: 99%
“…HHV-6 integration into human chromosomes may drive human disease via mechanisms such as chromosomal instability or epigenetic effects. 24 Telomeres carrying integrated HHV-6 may be unstable, leading to deletions, 25 and telomere length has important implications for chromosomal stability and cell viability. 26 Indeed, disruption in telomeres is associated with conditions ranging from pulmonary to hematologic diseases.…”
Section: Discussionmentioning
confidence: 99%